The Effectiveness in Learning of Writing Short Stories in the Covid-19 Outbreak Using Chamilo Media Based on Information Acquisition Type - Farokhi, Desti Atika; Haryadi, Haryadi (Universitas Negeri Semarang, 2021)
The students’ writing skills need to be considered by the teacher because writing skills are complex skills that can support students' academic achievements. The blended learning model with Chamilo media has been used in learning activities to write short stories in the Covid-19 outbreak. This study aims to determine the effectiveness of learning to write short stories in the Covid-19 outbreak by using a blended learning model with Chamilo media based on type of information acquisition type in vocational school students. The research design used is quasi-experimental with a population is XI grade students of SMK in 2020/2021 academic year. The data collection techniques use test and non-test techniques. The test technique has been carried out by measuring the skills of students in writing short stories, while non-test techniques has been carried out by using questionnaires, observation, and documentation. The data are analyzed using the T-test and analysis of variance (Anova). The results of the study proved that the use of the blended learning model with Chamilo media is effective in learning to write short stories in the Covid-19 outbreak based on the information acquisition type in vocational students. The research benefits provide theoretical and practical advantages. Theoretically, this research can enrich the theory of learning to write short stories in the Covid-19 outbreak by using a combination of blended learning models with Chamilo media. The importance of this research for educators is to increase a sense of responsibility for the quality of education in the era of the Covid-19 outbreak.